2002
DOI: 10.1051/forest:2002008
|View full text |Cite
|
Sign up to set email alerts
|

Analyse r�trospective de la croissance radiale et mise en relation avec le bilan hydrique dans un dispositif d'intensit� d'�claircie de pin maritime dans les Landes de Gascogne

Abstract: Résumé -En utilisant la technique dendrochronologique, une analyse rétrospective de la croissance radiale a été effectuée en 1998 sur un dispositif sylvicole de pin maritime (Pinus pinaster) des Landes de Gascogne destiné à étudier l'influence sur la croissance de diffé-rents régimes d'éclaircie. Ce dispositif installé en 1967 dans un peuplement de 19 ans, ayant actuellement 52 ans, avait été suivi pendant 12 ans. Il comprend 5 modalités d'intensité d'éclaircie avec 5 répétitions. Cette étude dendroécologique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This medium-term consequence of thinning has been reported in different species (Misson et al 2003;Kohler et al 2010;Sohn et al 2013) and likely resulted from tree structural changes, such as increased foliage area and fine root biomass (Sohn et al 2013). Benefits of thinning could be maintained by successive operations, as previously suggested by Le Goff and Ottorini (1993) and Timbal (2002) in Fagus and Pinus, respectively.…”
Section: Effect Of Thinning On the Climate-growth Relationshipmentioning
confidence: 60%
See 2 more Smart Citations
“…This medium-term consequence of thinning has been reported in different species (Misson et al 2003;Kohler et al 2010;Sohn et al 2013) and likely resulted from tree structural changes, such as increased foliage area and fine root biomass (Sohn et al 2013). Benefits of thinning could be maintained by successive operations, as previously suggested by Le Goff and Ottorini (1993) and Timbal (2002) in Fagus and Pinus, respectively.…”
Section: Effect Of Thinning On the Climate-growth Relationshipmentioning
confidence: 60%
“…This result agrees with Misson et al (2003) and Sohn et al (2013), who found a smaller relative growth reduction induced by severe drought in recently thinned stands. Conversely, Timbal (2002) reported a greater drought-induced reduction in the absolute growth of heavily thinned stands. Kohler et al (2010) and McDowell et al (2006) also reported this higher absolute decrease but additionally emphasized the occurrence of a lower relative decline, in line with our results.…”
Section: Effect Of Thinning On the Climate-growth Relationshipmentioning
confidence: 97%
See 1 more Smart Citation
“…The high productivity of the atlantica subspecies gives its forests an important economical value. Therefore, the majority of the recent reports on growth and yield models of the species have been focused on the Atlantic group (Falcão, 1997;Á lvarez-González et al, 1999Á lvarez-González et al, , 2002Rodríguez-Soalleiro et al, 2000;Timbal, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…However, in the last decade, dendrochronological methods are increasingly being used to analyze the effects of different factors on the growth of the maritime pine. Studies have been conducted on stands in southwest France (Timbal 2002), the west coast of Italy (De Micco et al 2007), coastal Tunisia (El Khorchani et al 2007), the northwestern Iberian Peninsula (Rozas et al 2011;Vieira et al 2009), central and centraleastern Spain (Bogino and Bravo 2008;Candel-Pérez et al 2012) and the mountains in southeastern Spain (Sánchez-Salguero et al 2010). In general terms, they are quite young forests, very few of them surpassing 100 years of age (Bogino and Bravo 2008).…”
mentioning
confidence: 99%